Water-damage-resistant high-performance asphalt mixture doped with fibers and preparation method of water-damage-resistant high-performance asphalt mixture

By adding basalt fibers and polyacrylonitrile fibers to the asphalt mixture, the water stability and pavement performance of the asphalt mixture are improved, the problem of peeling off asphalt mixture on rainy days is solved, and the passability and service life of the asphalt pavement are enhanced.

CN119285276APending Publication Date: 2025-01-10CHINA RAILWAY 16TH BUREAU GRP ROAD & BRIDGE ENG CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411385495.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing asphalt mixtures are prone to pore water pressure on rainy days, causing asphalt and aggregate to peel off, leading to diseases such as pavement surfaces, pits and grooves, affecting the service level of roads, and have high temperature stability, low temperature bending resistance, water stability, and durability. The properties and anti-slip safety are contradictory, making it difficult to design a mixture that suits the actual road environment.

Method used

Use water-resistant composite fiber high-performance bituminous mixture, including 96-97% asphalt aggregate and 3-4% asphalt, and add 0.16-0.24% of composite fibers, specifically basalt fibers and polyacrylonitrile fibers, and heat them. The asphalt is evenly mixed with preheated aggregates and fibers to improve compactness and water stability and enhance road surface performance.

Benefits of technology

It improves the high-temperature stability, low-temperature bending resistance, durability and anti-slip safety of asphalt mixture, enhances the passability and service life of asphalt pavement, and ensures good road performance under different water environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of preparation of asphalt mixtures for road engineering, and discloses a water-damage-resistant high-performance asphalt mixture doped with fibers and a preparation method of the water-damage-resistant high-performance asphalt mixture. The asphalt mixture provided by the invention is a water-damage-resistant fiber-doped high-performance asphalt mixture, and the asphalt consumption and the void ratio of the asphalt mixture are in the optimal proportion; particularly, the asphalt mixture interacts with aggregate with set gradation, and basalt and polyacrylonitrile fiber are mixed for use, so that the bonding effect between the aggregate and asphalt is better, the overall compactness and water stability of the asphalt mixture are further improved, and meanwhile, other comprehensive pavement performance of the asphalt mixture is also improved; and the asphalt pavement has high-temperature stability, low-temperature bending resistance, durability and anti-skid safety, so that the traffic capacity and the service life of the asphalt pavement are enhanced, and the asphalt pavement can have good pavement performance in different water environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of asphalt mixture preparation for road engineering, and in particular to a water-damage-resistant fiber-blended high-performance asphalt mixture and a preparation method thereof. Background Art

[0002] When cars are driving on rainy days, great pore water pressure is generated inside the pavement material, which accelerates the peeling of asphalt and aggregate, resulting in defects such as roughness and potholes on the asphalt pavement, greatly affecting the road service level.

[0003] Asphalt pavement water damage is a phenomenon in which the mechanical properties of asphalt mixture materials are reduced due to the presence of liquid or gaseous water. The specific forms of damage are peeling, loosening, falling particles, and water erosion. Among them, peeling is the first stage of asphalt pavement water damage. The repeated action of traffic loads causes the asphalt mixture to loosen and fall particles, and then forms large-scale water erosion. It is particularly important to study how to improve the road performance of asphalt mixtures, such as high temperature stability, low temperature bending and tensile resistance, water stability, durability and anti-skid safety, and adopt measures to enhance the traffic capacity and service life of asphalt pavements.

[0004] The gradation and type of asphalt mixture mineral aggregates widely used now are mainly designed by (AC, SMA) design methods. In terms of high temperature stability, low temperature crack resistance, skid resistance, durability, fatigue performance, etc., they are often contradictory or mutually restrictive. Taking care of one performance is likely to reduce the performance of the other. This leads to how to design an asphalt mixture design method that more realistically simulates actual road conditions, so that the force of the asphalt mixture is more in line with the actual road use environment and process, which is currently a top priority. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide a water-damage-resistant fiber-blended high-performance asphalt mixture and a preparation method thereof, so that the asphalt mixture can improve its low-temperature water-damage resistance.

[0006] In order to solve the above-mentioned technical problems / achieve the above-mentioned purposes or at least partially solve the above-mentioned technical problems / achieve the above-mentioned purposes, as the first aspect of the present application, a water-resistant and fiber-blended high-performance asphalt mixture is provided, comprising asphalt aggregate and a composite fiber additive; the asphalt aggregate comprises asphalt and aggregate, wherein the volume proportion of the aggregate is 96-97%, and the volume proportion of the asphalt is 3-4%; the composite fiber additive comprises basalt fiber and polyacrylonitrile fiber, and the volume percentages of the two are independently 0.16-0.24% of the volume of the asphalt aggregate.

[0007] Optionally, the gradation range of the aggregate is as follows:

[0008] 37.5mm corresponds to a quality pass rate of 99-100%;

[0009] 26.5mm corresponds to a quality pass rate of 95-100%;

[0010] 19mm corresponds to a quality pass rate of 78-82%;

[0011] 13.2mm corresponds to a quality pass rate of 66-72%;

[0012] 9.5mm corresponds to a quality pass rate of 51-58%;

[0013] 4.75mm corresponds to a quality pass rate of 26-32%;

[0014] 2.36mm corresponds to a quality pass rate of 17-24%;

[0015] 1.18mm corresponds to a quality pass rate of 14-19%;

[0016] 0.6mm corresponds to a quality pass rate of 12-16%;

[0017] 0.3mm corresponds to a quality pass rate of 11-15%;

[0018] 0.15mm corresponds to a quality pass rate of 10-12%;

[0019] The corresponding quality pass rate of 0.075mm is 2-5%.

[0020] Further optionally, the aggregate includes coarse aggregate, fine aggregate and mineral powder, the coarse aggregate and fine aggregate include limestone aggregate, and the mineral powder includes limestone mineral powder. Further optionally, the coarse aggregate is selected from limestone aggregate with a particle size of 5 to 25 mm, the fine aggregate is selected from limestone aggregate with a particle size of 0 to 5 mm, and the mineral powder is selected from limestone mineral powder with a particle size of less than 0.075 mm.

[0021] Optionally, the length of the basalt fiber is 12±1.5 mm, the tensile strength is ≥1200 MPa, and the ultimate elongation is ≥3.1% ≥2.8%; the length of the polyacrylonitrile fiber is 12±1.5 mm, the tensile strength is ≥500 MPa, and the ultimate elongation is ≥20%. Further optionally, the volume ratio of the basalt fiber to the polyacrylonitrile fiber is 2:3.

[0022] Optionally, after the asphalt mixture is compacted, the aggregate gap ratio is 12.5-13.5%, the asphalt filling ratio is 67-70%, the powder-rubber ratio is 0.90-1.02, and the void ratio is 3.9-4.1%.

[0023] Optionally, the asphalt is selected from Grade A petroleum asphalt.

[0024] As a second aspect of the present application, a method for preparing the asphalt mixture is provided, comprising:

[0025] After the asphalt is heated, it is added to the preheated aggregate that has been stirred evenly and the stirring is continued. Then, the preheated composite fiber is added and stirred evenly to obtain the asphalt mixture.

[0026] The asphalt mixture provided in the present application is a water-resistant, fiber-blended, high-performance asphalt mixture, in which the asphalt dosage and void ratio of the asphalt mixture are in an optimal ratio; in particular, its interaction with the aggregate of the set grade, coupled with the use of basalt and polyacrylonitrile fiber blending, makes the bonding effect between the above-mentioned aggregate and asphalt better, thereby improving the overall compactness and water stability of the asphalt mixture, while also improving other comprehensive road performance of the asphalt mixture, such as high-temperature stability, low-temperature flexural and tensile strength, durability and anti-skid safety, thereby enhancing the traffic capacity and service life of the asphalt pavement, etc., so that the asphalt pavement can have good road performance in different water environments. DETAILED DESCRIPTION

[0027] The present application discloses a water-resistant fiber-blended high-performance asphalt mixture and a preparation method thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0028] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.

[0029] In the first aspect of the present application, a water-resistant, fiber-blended, high-performance asphalt mixture is provided, comprising asphalt aggregate and a composite fiber additive; the asphalt aggregate comprises asphalt and aggregate, wherein the volume proportion of the aggregate is 96-97%, and the volume proportion of the asphalt is 3-4%; the composite fiber additive comprises basalt fiber and polyacrylonitrile fiber, and the volume percentages of the two are independently 0.16-0.24% of the volume of the asphalt aggregate.

[0030] In certain embodiments of the present application, the gradation range of the aggregate is as follows:

[0031] 37.5mm corresponds to a quality pass rate of 99-100%;

[0032] 26.5mm corresponds to a quality pass rate of 95-100%;

[0033] 19mm corresponds to a quality pass rate of 78-82%;

[0034] 13.2mm corresponds to a quality pass rate of 66-72%;

[0035] 9.5mm corresponds to a quality pass rate of 51-58%;

[0036] 4.75mm corresponds to a quality pass rate of 26-32%;

[0037] 2.36mm corresponds to a quality pass rate of 17-24%;

[0038] 1.18mm corresponds to a quality pass rate of 14-19%;

[0039] 0.6mm corresponds to a quality pass rate of 12-16%;

[0040] 0.3mm corresponds to a quality pass rate of 11-15%;

[0041] 0.15mm corresponds to a quality pass rate of 10-12%;

[0042] The corresponding quality pass rate of 0.075mm is 2-5%.

[0043] Compared with the conventional gradation in the field, the gradation design of the present application adds 37.5mm, 26.5mm and other large sieve hole gradation requirements, which significantly reduces the subsequent pass rate of small-size sieve holes. This design concept can not only make the asphalt mixture pavement more solid, but also has obvious help for the pavement's resistance to water damage. In some other embodiments of the present application, the gradation range of the aggregate is as follows:

[0044] 37.5mm corresponds to a quality pass rate of 99.73%;

[0045] 26.5mm corresponds to a quality pass rate of 99.66%;

[0046] The corresponding quality pass rate of 19mm is 80.73%;

[0047] 13.2mm corresponds to a quality pass rate of 69.79%;

[0048] 9.5mm corresponds to a quality pass rate of 56.70%;

[0049] 4.75mm corresponds to a quality pass rate of 29.60%;

[0050] 2.36mm corresponds to a quality pass rate of 21.80%;

[0051] 1.18mm corresponds to a quality pass rate of 17.59%;

[0052] The corresponding quality pass rate of 0.6mm is 14.73%;

[0053] 0.3mm corresponds to a quality pass rate of 12.71%;

[0054] 0.15mm corresponds to a quality pass rate of 11.78%;

[0055] The corresponding quality pass rate of 0.075mm is 3.86%.

[0056] In certain embodiments of the present application, the aggregate includes coarse aggregate, fine aggregate and mineral powder, the coarse aggregate and fine aggregate are both limestone aggregates, the limestone coarse aggregate is selected from limestone aggregates with a particle size of 5 to 25 mm, the limestone fine aggregate is selected from limestone aggregates with a particle size of 0 to 5 mm (mechanical sand), the mineral powder is selected from limestone mineral powder, and further selected from limestone mineral powder with a particle size of less than 0.075 mm, which can make the asphalt and the aggregate better bonded; in other embodiments of the present application, the limestone coarse aggregate is selected from four particle size specifications of 5 to 10 mm, 10 to 15 mm, 15 to 20 mm and 20 to 25 mm respectively;

[0057] In certain embodiments of the present application, the volume proportions of aggregates of various particle sizes and asphalt in the asphalt aggregate are: coarse aggregate 69.15%, fine aggregate 19.43%, mineral powder 7.82%, and asphalt 3.60%; among the coarse aggregate, the particle size of 20-25 mm accounts for 9.55%, the particle size of 15-20 mm accounts for 21.10%, the particle size of 10-15 mm accounts for 11.62%, and the particle size of 5-10 mm accounts for 26.88%; the fine aggregate (machine-made sand) of 0-5 mm particle size accounts for 19.43%.

[0058] In some embodiments of the present application, the basalt fiber is selected from basalt chopped fibers, more specifically, the length of the basalt fiber is 12±1.5 mm, the tensile strength is ≥1200 MPa, and the ultimate elongation is ≥2.8% at 3.1%; in some other embodiments of the present application, the length of the polyacrylonitrile fiber is 12±1.5 mm, the tensile strength is ≥500 MPa, and the ultimate elongation is ≥20%. In some other embodiments of the present application, the volume ratio of the basalt fiber to the polyacrylonitrile fiber is 2:3.

[0059] In some embodiments of the present application, the aggregate gap ratio is 12.5-13.5%, the asphalt filling ratio is 67-70%, and the powder-rubber ratio is 0.90-1.02. In some other embodiments of the present application, after the asphalt mixture is compacted, the void ratio is 3.9-4.1%.

[0060] In certain embodiments of the present application, the asphalt is selected from Grade A petroleum asphalt, such as No. 70 Grade A petroleum asphalt.

[0061] In a second aspect of the present application, a method for preparing the asphalt mixture is provided, comprising:

[0062] After the asphalt is heated, it is added to the preheated aggregate that has been stirred evenly and the stirring is continued. Then, the preheated composite fiber is added and stirred evenly to obtain the asphalt mixture.

[0063] In the present application, the asphalt mixture provided meets the following performance index requirements: the water stability index Marshall water immersion residual stability is not less than 94%; the low temperature performance index freeze-thaw cycle strength ratio is not less than 90%, and the stiffness modulus is not greater than 8300MPa. The asphalt mixture described in the present application is resistant to water damage at low temperatures.

[0064] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.

[0065] The following is a further description of a water-damage-resistant fiber-blended high-performance asphalt mixture and a preparation method thereof provided in the present application.

[0066] Embodiment 1:

[0067] 1. Raw materials

[0068] Basalt: limestone commercially available from stone factories, with technical indicators shown in Table 1.

[0069] Mineral powder: commercially available limestone mineral powder, the technical indicators are shown in Table 2.

[0070] Asphalt: Commercially available No. 70 Grade A asphalt was tested for relevant technical indicators of asphalt according to the “Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering”. The technical indicators are shown in Table 3.

[0071] Fiber: Basalt chopped fiber and polyacrylonitrile fiber are used. The fiber is clean and smooth, meeting the requirements of "Fiber for Asphalt Pavement". The technical indicators are shown in Table 4 and Table 5.

[0072] Table 1 Technical indicators of coarse and fine aggregates of limestone

[0073]

[0074] Table 2 Technical indicators of mineral powder

[0075]

[0076] Table 3 Technical indicators of 70#A grade petroleum asphalt

[0077]

[0078]

[0079] Table 4 Basalt fiber performance indicators

[0080]

[0081] Table 5 Performance indexes of polyacrylonitrile fiber

[0082]

[0083] 2. Mix ratio design

[0084] The proportion of aggregate and asphalt in asphalt aggregate is shown in Table 6, and the quality pass rate of each aggregate is shown in Table 7;

[0085] Table 6: The proportion of aggregates of various particle sizes and asphalt in the total volume of asphalt aggregates in the examples

[0086]

[0087] Among them, the volume ratio of basalt fiber to polyacrylonitrile fiber is 2:3, and the volume content of composite fiber accounts for 0.4% of the total asphalt aggregate.

[0088] Table 7 The quality pass rate of each aggregate in the embodiment

[0089]

[0090] 3. Preparation process

[0091] The above-mentioned material is used, after the asphalt is heated, it is added to the preheated aggregate that is stirred evenly and continues to be stirred, and then the preheated composite fiber is added and stirred evenly to obtain the asphalt mixture.

[0092] The number of gyratory compaction is determined according to the traffic volume level. Superpave not only has corresponding constraints on the PG grading of the binder for different cumulative equivalent axle load times (ESALS), but also stipulates the number of gyratory compaction. The number of gyratory compaction designed by Superpave is shown in Table 8, and the gyratory compaction data of asphalt mixture when the asphalt volume content is 3.60% is shown in Table 9;

[0093] Table 8 Superpave design rotation compaction times

[0094]

[0095] Table 9 Gyratory compaction data of asphalt mixture when the asphalt volume content is 3.60%

[0096]

[0097]

[0098] After compaction, the aggregate gap ratio is 12.5-13.5%, the asphalt filling ratio is 67-70%, the powder-rubber ratio is 0.90-1.02, and the void ratio is 3.9-4.1%.

[0099] Comparative Example 1:

[0100] The process of Example 1 is referred to, except that only basalt fiber is used, the total fiber content remains unchanged at 0.4%, and the rest is consistent with Example 1.

[0101] Comparative Example 2:

[0102] The process of Example 1 is referred to, except that basalt fiber and polyester fiber are used in a composite material with a volume ratio of 2:3 and a total dosage of 0.4%. Other aspects are consistent with Example 1.

[0103] Experimental example: Road performance benefit analysis

[0104] According to the performance research, reasonable upper and lower limits of satisfaction for the three indicators of the test are set, which are suitable for highway projects, so that the final comparison will not deviate from the actual needs; then the performance indicators are summarized and evaluated:

[0105]

[0106] In the formula:

[0107] d——efficiency coefficient;

[0108] d i ——score of single indicator;

[0109] Z ia ——Satisfaction value;

[0110] Z ib ——the actual value of the ith indicator;

[0111] Z ic ——values ​​are not allowed;

[0112] C, D——are constants, C is usually 40, and D is usually 60;

[0113] ——(Average) score of individual indicator.

[0114] Table 10 Parameter values ​​of road performance evaluation indicators

[0115]

[0116]

[0117] The analysis results are shown in Table 11 below;

[0118] Table 11 Performance benefit analysis results

[0119]

[0120] Note: The smaller the stiffness modulus, the better the bending tensile performance;

[0121] According to the above table, the composite of basalt fiber and polyacrylonitrile fiber is significantly better than single basalt fiber (Comparative Example 1) and other types of composite fibers (Comparative Example 2) in terms of stiffness modulus and residual stability after immersion in water. Although the freeze-thaw cycle strength ratio is lower than that of Comparative Example 2, according to the overall performance benefit analysis of the formula, its index score is It is higher than the other two comparison examples, indicating that when the asphalt mixture of the present application is applied to actual road surfaces, it has more obvious advantages in facing low-temperature water damage.

[0122] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A water-damage-resistant fiber-blended high-performance asphalt mixture, characterized in that: It includes asphalt aggregate and composite fiber additive; the asphalt aggregate includes asphalt and aggregate, wherein the volume proportion of the aggregate is 96-97%, and the volume proportion of the asphalt is 3-4%; the composite fiber additive includes basalt fiber and polyacrylonitrile fiber, and the volume percentages of the two are independently 0.16-0.24% of the volume of the asphalt aggregate.

2. The asphalt mixture according to claim 1, characterized in that: The grading range of the aggregate is as follows: the corresponding mass pass rate of 37.5mm is 99-100%; the corresponding mass pass rate of 26.5mm is 95-100%; the corresponding mass pass rate of 19mm is 78-82%; the corresponding mass pass rate of 13.2mm is 66-72%; the corresponding mass pass rate of 9.5mm is 51-58%; the corresponding mass pass rate of 4.75mm is 26-32%; the corresponding mass pass rate of 2.36mm is 17-24%; the corresponding mass pass rate of 1.18mm is 14-19%; the corresponding mass pass rate of 0.6mm is 12-16%; the corresponding mass pass rate of 0.3mm is 11-15%; the corresponding mass pass rate of 0.15mm is 10-12%; the corresponding mass pass rate of 0.075mm is 2-5%.

3. The asphalt mixture according to claim 1 or 2, characterized in that: The aggregate comprises coarse aggregate, fine aggregate and mineral powder, the coarse aggregate and fine aggregate comprise limestone aggregate, and the mineral powder comprises limestone mineral powder.

4. The asphalt mixture according to claim 3, characterized in that: The coarse aggregate is selected from limestone aggregate with a particle size of 5 to 25 mm, the fine aggregate is selected from limestone aggregate with a particle size of 0 to 5 mm, and the mineral powder is selected from limestone mineral powder with a particle size of less than 0.075 mm.

5. The asphalt mixture according to claim 1, characterized in that: The length of the basalt fiber is 12±1.5 mm, the tensile strength is ≥1200 MPa, and the ultimate elongation is ≥3.1% and ≥2.8%; the length of the polyacrylonitrile fiber is 12±1.5 mm, the tensile strength is ≥500 MPa, and the ultimate elongation is ≥20%.

6. The asphalt mixture according to claim 1 or 5, characterized in that: The volume ratio of the basalt fiber to the polyacrylonitrile fiber is 2:

3.

7. The asphalt mixture according to claim 1, characterized in that: The asphalt is selected from Grade A petroleum asphalt.

8. The asphalt mixture according to claim 1, characterized in that: After the asphalt mixture is compacted, the aggregate gap ratio is 12.5-13.5%, the asphalt filling ratio is 67-70%, the powder-rubber ratio is 0.90-1.02, and the void ratio is 3.9-4.1%.

9. The method for preparing asphalt mixture according to claim 1, characterized in that: include: After the asphalt is heated, it is added to the preheated aggregate that has been stirred evenly and the stirring is continued. Then, the preheated composite fiber is added and stirred evenly to obtain the asphalt mixture.

Citation Information

Cited By

  • Low-noise water-damage-resistant asphalt mixture and preparation method thereof

    CN120441237A